2005
DOI: 10.1016/s0002-9440(10)62326-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered Epithelial Cell Lineage Allocation and Global Expansion of the Crypt Epithelial Stem Cell Population Are Associated with Ileitis in SAMP1/YitFc Mice

Abstract: Crohn's disease is characterized by cycles of mucosal injury and ulceration followed by epithelial regeneration and restoration of normal epithelial function. In this study, we examined whether ileitis in SAMP1/YitFc mice, a recombinant-inbred line that spontaneously develops ileitis resembling human Crohn's disease, was associated with alterations in normal patterns of epithelial differentiation or changes in epithelial regeneration after experimental injury. Increased numbers of Paneth, goblet, and intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 62 publications
(57 reference statements)
5
37
0
Order By: Relevance
“…Second, mucosal lymphocytes from the MLNs of SAMP mice proliferate and produce cytokines after stimulation with SPF-FA. Such immunobacterial interactions are expected in vivo, because SAMP mice display an early epithelial cell defect (24,25) that allows for a constant cross-talk between commensal bacteria and the gut immune system, which is in line with previous studies from both humans and mice (7,10,27). Third, our results indicate that different components of the mucosal immune system have unequal dependence on the presence of commensal bacteria.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Second, mucosal lymphocytes from the MLNs of SAMP mice proliferate and produce cytokines after stimulation with SPF-FA. Such immunobacterial interactions are expected in vivo, because SAMP mice display an early epithelial cell defect (24,25) that allows for a constant cross-talk between commensal bacteria and the gut immune system, which is in line with previous studies from both humans and mice (7,10,27). Third, our results indicate that different components of the mucosal immune system have unequal dependence on the presence of commensal bacteria.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, there was selective suppression of the intestinal Th2 cytokines IL-5 and IL-13, whereas no effect was seen on others, i.e., IFN-␥. Finally, we have recently shown that SAMP mice display an epithelial cell defect that occurs before the development of histological injury (24). Because this defect is also present in GF mice (25), it therefore occurs independently of colonization by commensal flora.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, the relationship between crypt hyperplasia and goblet cell depletion phenotypes observed in other models of intestinal inflammation appears to be complex: for example, the immune system-mediated pathology that occurs during murine helminth infections results in both crypt and goblet cell hyperplasia (2,34,35). Moreover, in SAMP1/YitFc mice which develop spontaneous Crohn's disease-like ileitis (72), inflammationinduced crypt elongation is associated with the expansion of secretory lineages, including Paneth and goblet cells (72). Taken together, these studies suggest that the mechanisms underlying the depletion of mature goblet cells during C. rodentium infection may involve processes that are independent of, but coordinated with, the induction of crypt hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate cells are rarely seen in normal adult intestinal epithelium, but they have been reported in cases of intestinal infection, inflammation, and inhibition of Notch signaling (36,39,42). The function of these secretory cells is not clear.…”
Section: A' A''mentioning
confidence: 99%